Evaluation of Integrated Financial Management Information System (IFMIS) in Tanzania - Laizer E; Suomi R (United Kingdom, 2022)
The purpose of this study is to evaluate the integrated financial management information system (IFMIS) in Tanzania's Local Authorities. In the 1990s, Sub-Saharan African governments and other developing countries embarked on plans to automate their business processes. Public financial management is one of the areas that were automated. The first author has been involved in the evaluation of IFMIS in the governments of Lesotho and Malawi. He has also provided IFMIS support to the Tanzania's Local Authorities and Namibia Tender Board. During these assignments, different data related to IFMIS success and challenges were collected. The methods used for data collection were; desk review i.e. reviewing documents related to business processes analysis, functional requirements, user acceptance tests, government-vendor contracts, reports produced from systems, project charter, and other documents related to IFMIS. We also conducted interviews with different users confirming their involvement and the use of IFMIS. Vendors were also interviewed to find out the approaches used in system design and implementation. System access was adopted to see the actual settings such as payments, budget rules, user matrix, and chart of accounts, budget planning and management. IFMIS has been implemented for more than 18 years in Tanzania; however, some important objectives are yet to be realized. This study uses data collected in 2012 from Tanzania's Local Authorities; the first author worked with Local Authorities as an ICT consultant. The main challenges of IFMIS that were identified are related to interoperability, systems proliferation, running manual and automated systems in parallel, a lack of IFMIS policies, a lack of standards and principles. Among the main objectives of IFMIS are timely and accurate reports for making decisions related to finance management. Furthermore, IFMIS reports are supposed to support the process of building transparency, accountability, and the reduction of corruption within governments. The current challenges facing IFMIS hinder the achievement of its core objectives. The study adopted System Development Life Cycle (SDLC) as a tool for evaluating the IFMIS used by Tanzania's Local Authorities.
PROCEEDINGS OF THE 12TH EUROPEAN CONFERENCE ON MANAGEMENT, LEADERSHIP AND GOVERNANCE (ECMLG 2016)